The Effect of Energy Patches on Substrate Utilization in Collegiate Cross-Country Runners - FIDDLER, RYAN E. (Int J Exerc Sci, 2011)
It is well established that an increased capacity of skeletal muscle to oxidize fatty acids can spare glycogen and delay the onset of fatigue in mild- to moderate-intensity exercise. The purpose of the following study was to examine the effect of LifeWave® energy patches on non-protein substrate utilization in Division-1 cross-country runners. To determine the effect of the patches subjects were pretested to establish baselines and randomly assigned to an experimental (EX) or placebo (PL) group. Twenty-two trained male (n = 11; mean ± SD, age = 21.1 ± 2.6years, height = 179.6 ± 4.2cm, body mass = 71.4 ± 7.4kg, VO(2max) = 72.6 ± 7.1mL·kg-1·min-1) and female (n = 11; mean ± SD, age = 21.5 ± 2.4years, height = 166.7 ± 5.7cm, body mass = 53.7 ± 3.2kg, VO(2max) = 63.6 ± 6.9mL·kg-1·min-1) cross-country runners volunteered to participate in the study. Dependent variables included maximal oxygen consumption (VO(2max)), rating of perceived exertion (RPE), respiratory exchange ratio (RER), maximum heart rate (HRmax), and time to exhaustion (TTE). Results indicated there were no significant differences between the EX and PL groups at posttesting for RPE, TTE, HRmax, or VO(2max). RER was found to be significantly higher for the EX group compared to the PL group during stage 1 of the Bruce-protocol graded exercise test (p = 0.02). Based on the limited available research regarding LifeWave® energy patches effect on non-protein substrate utilization during aerobic exercise there appears to be no performance enhancing benefits.